A note on the mapping theorem of essential pseudospectra on a Banach space - Ammar, Aymen; Veeramani, S. (Ukrains’kyi Matematychnyi Zhurnal, 2024)
UDC 517.98 The main goal of the paper is to determine some basic properties of the essential pseudospectrum of a bounded linear operator A defined on a Banach space X. We also prove two different versions of the essential pseudospectral mapping theorem.